POST-WAR RECONSTRUCTION OF STAROSTYNSKY DISTRICTS IN UKRAINE: FINANCIAL ASPECT - Melnyk, Kostyantyn (Scientific Journal of Polonia University, 2023)
Within the framework of the study, the content of the concept of “post-war reconstruction of Starostynsky districts in Ukraine” was considered, which should be based on a resource approach. This approach about understanding by local self-government bodies (and elders in particular) of the importance of developing a multi-vector policy for the development of rural and settlement territories after the end of the war with russia. The author of the article emphasizes that there is a direct relationship between the financial capacity of Starostynsky districts and the speed of recovery (economic, technological, social and cultural) of the territories within these districts. The article analyzes the problematic issues of the post-war reconstruction of Starostynsky districts, as well as the main tools: 1) to ensure the reconstruction of the territories of villages and towns affected by the war, which are part of Starostynsky districts; 2) to find financial resources and opportunities sufficient to fulfill the current and prospective tasks of the development of Starostynsky districts in Ukraine (fundraising is defined as one of the key tools). Twenty forms of post-war support for enterprises, farmers, and households in the territories of villages and settlements have been proposed, which will contribute to the creation of an investment attractive environment in Starostynsky districts. Attention was drawn to the importance of stimulating fast-growing, high-tech industries, programs to support the transition of business to the circular economy, and the importance of cooperation of all branches of government, including starosta as key players in the system of local self-government, to ensure the financial capacity of Starostynsky districts.